In my mother's house : a daughter's story - Chernin, Kim (Purdue University Press, 2019)
"In My Mother's House depicts a profound, intergenerational struggle between a powerful, politically engaged mother, Rose, and her spiritually inclined poet and writer daughter, Kim. Framing this collision are two other generations. There is Rose's mother from the shtetl, a broken woman regularly beaten by her husband but the source of the family's stories. And Kim's daughter, a second-generation, fully assimilated girl of eight at the time the book begins. Four generations, from the shtetl to an affluent intellectual household in Berkeley, California, the story is a historical record and reckoning between the old activist left and a beginning feminist movement. The double narrative allows Kim to explore the evolving relationship between mother and daughter, who, through their storytelling, are brought to a profound understanding and reconciliation"--